KEPEMIMPINAN DALAM PERSPEKTIF ISLAM KEINDONESIAAN - Dr. Muh. Haras Rasyid, M.Ag (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Leadership issues are important in human life. If a group of people or a nation in a region have no leader, there will be a chaos. How important The leader, Allah Swt. Has created the first man and named him as a leader. That’s why leadership with all The aspects, can be said as Sunnatullah. As in Indonesia, leadership, especially the problem of choosing a leader, is a substantial issues that needs to be considered by all parties.Imagine, Indonesia is a predominantly Muslim country, but its main foundation in the life of the country is Pancasila and the 1945 Constitution, not the Qur'an and hadith as the main and first source of law in Islamic teachings. Because the issue of choosing leaders in Indonesia, including the areas of national and state life, constitutional references or formal law in the implementation of leader electorate is Pancasila and the 1945 Constitution. However, and no mistake the teachings of religions recognized in Indonesia, especially the teachings which contained in the Qur'an 'An and hadith can serve as a moral foundation.